Women with learning disabilities and access to cervical screening: retrospective cohort study using case control methods - Stanistreet Debbi; Reynolds Fiona; Elton Peter (BMC, 2008)
Abstract Background Several studies in the UK have suggested that women with learning disabilities may be less likely to receive cervical screening tests and a previous local study in had found that GPs considered screening unnecessary for women with learning disabilities. This study set out to ascertain whether women with learning disabilities are more likely to be ceased from a cervical screening programme than women without; and to examine the reasons given for ceasing women with learning disabilities. It was carried out in Bury, Heywood-and-Middleton and Rochdale. Methods Carried out using retrospective cohort study methods, women with learning disabilities were identified by Read code; and their cervical screening records were compared with the Call-and-Recall records of women without learning disabilities in order to examine their screening histories. Analysis was carried out using case-control methods - 1:2 (women with learning disabilities: women without learning disabilities), calculating odds ratios. Results 267 women's records were compared with the records of 534 women without learning disabilities. Women with learning disabilities had an odds ratio (OR) of 0.48 (Confidence Interval (CI) 0.38 - 0.58; X2: 72.227; p.value <.001) of receiving a cervical screening test; an OR of 2.05 (CI 1.88 - 2.22; X2: 24.236; p.value <.001) of being ceased from screening; and an OR of 0.14 (CI 0.001 - 0.28; X2: 286.341; p.value <0.001 of being a non-responder compared to age and practice-matched women without learning disabilities. Conclusion The reasons given for ceasing and/or not screening suggest that merely being coded as having a learning disability is not the sole reason for these actions. There are training needs among smear takers regarding appropriate reasons not to screen and providing screening for women with learning disabilities.